The Model of Perceived Organizational Support, Employee Engagement, Organizational Citizenship Behavior in the Environment Directorate General of Sea Transportation - Afendi, Ali; Wibowo, Ari; Wangloan, Euis Happy (International Review of Management and Marketing, 2020)
The role of transportation is very important in supporting the development process to support public economic activities both in rural and urban areas in Indonesia. Adequate transportation facilities are expected to eliminate the isolation and create a stimulant in each region to be more advanced and developed evenly in all sectors of life, trade, industry, education, health, and other sectors. So it will always be needed repair and upgrading of public transport services both in terms of facilities, security systems, procedures, and human resources support. Moreover, if faced with a high number of transport accidents in Indonesia, the results showed that perceived organizational support and Employee Engagement simultaneously have a positive and significant effect on organizational citizenship behavior with a contribution of 61%. The Employee Engagement partially has more dominant influence on organizational citizenship behavior compared to perceived organizational support. The managerial implication of the results of this study was that to reach higher organizational citizenship behavior in Environment Directorate General of SEA Transportation, leaders must emphasize in Employee Engagement with removing silos as the main dimension to focus on. Keywords: Perceived Organizational Support, Employee Engagement, Organizational Citizenship Behavior JEL Classifications: O32, M54, N75 DOI: https://doi.org/10.32479/irmm.9145